2000
DOI: 10.1006/dbio.2000.9873
|View full text |Cite
|
Sign up to set email alerts
|

Different Activities of the Frizzled-Related Proteins frzb2 and sizzled2 during Xenopus Anteroposterior Patterning

Abstract: In a search for factors that regulate patterning of the Xenopus anteroposterior (A/P) axis, particularly the anterior ectoderm, we isolated two members of the Frizzled-related protein (FRP) gene family that are thought to encode antagonists of Wnt signaling. frzb2 is expressed in head mesoderm while sizzled2 is expressed in ventral ectoderm and mesoderm, tissues that modulate anterior fates. Consistent with a role for these genes in A/P patterning, ectopically expressed frzb2 inhibited head formation, while si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 63 publications
1
58
0
1
Order By: Relevance
“…More recently, this group has shown that Dkk-1 and crescent, which are both expressed in the organizer region, can induce cardiogenesis in ventral marginal zone tissue (Schneider and Mercola 2001). Consistent with the idea that Wnt signaling suppresses cardiogenesis in vivo, Sive and coworkers have shown that ectopic expression of FrzB family members can expand Nkx-2.5 gene expression in Xenopus embryos (Bradley et al 2000). Together with our own findings, these results suggest that heart induction can only take place in a region of the vertebrate embryo with low Wnt activity.…”
Section: A Wnt Activity Gradient From Posterior To Anterior Modulatesmentioning
confidence: 77%
“…More recently, this group has shown that Dkk-1 and crescent, which are both expressed in the organizer region, can induce cardiogenesis in ventral marginal zone tissue (Schneider and Mercola 2001). Consistent with the idea that Wnt signaling suppresses cardiogenesis in vivo, Sive and coworkers have shown that ectopic expression of FrzB family members can expand Nkx-2.5 gene expression in Xenopus embryos (Bradley et al 2000). Together with our own findings, these results suggest that heart induction can only take place in a region of the vertebrate embryo with low Wnt activity.…”
Section: A Wnt Activity Gradient From Posterior To Anterior Modulatesmentioning
confidence: 77%
“…The Lrp4-Wise complex can, in turn, modulate BMP activity (Lintern et al, 2009;Ohazama et al, 2010). It is worth noting that the DLMZ of the late blastula/early gastrula stage X. laevis embryo is characterized by the expression of a number of other secreted signaling agonists and antagonists, in addition to chordin, sizzled, cerberus, frzb1, bmp4 and wnt8; these include other canonical and non-canonical acting Wnts (Kuhl, 2002), the TGF inhibitor Follistatin (Fainsod et al, 1997;Iemura et al, 1998;Tashiro et al, 1991), the BMP inhibitor Noggin (Smith and Harland, 1992) and the Wnt inhibitors Dkk, SFRP2, Sizzled2 and Crescent (Bradley et al, 2000;Glinka et al, 1998;Semenov et al, 2001;Shibata et al, 2000), as well as membrane-bound signaling regulators such as Kremen (Nakamura and Matsumoto, 2008). qPCR analyses support the view that the differences in the effects of snail1, snail2 and twist1 MOs in the C2/C3 lineage are due to differences in their regulatory targets (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, only sFRP1 and -2 could block Wnt3a signaling in L cells (Wawrzak et al 2007). Several other studies have described possible biochemical and/or functional specificity of the sFRPs-Wnt interactions in different developmental models, including the neural tube (Galli et al 2006), somites (Lee et al 2000), vascular endothelium (Dennis et al 1999), and developing heart (Schneider and Mercola 2001), as well as during AP axial patterning of Xenopus embryos (Bradley et al 2000;Pera and De Robertis 2000).…”
Section: Mechanism Of Actionmentioning
confidence: 97%
“…A third subgroup of sFRPs has been identified in Xenopus, chick, and zebrafish, but not in mammals. Members of this subgroup are Sizzled, Sizzled2, and Crescent, and they share sequence similarities with the sFRP1, -2, and -5 subgroup (Pfeffer et al 1997;Salic et al 1997;Bradley et al 2000;Pera and De Robertis 2000;Houart et al 2002).…”
Section: Physical Properties and Structurementioning
confidence: 99%